A USABILITY STUDY OF A MOBILE CONTENT SHARING SYSTEM - CHUA, ALTON Y. K.; GOH, DION HOE-LIAN; RAZIKIN, KHASFARIYATI; LIM, EE-PENG (Journal of Mobile Multimedia, 2011)
We investigate the usability of MobiTOP (Mobile Tagging of Objects and People), a mobile location-based content sharing system. MobiTOP allows users to annotate real world locations with both multimedia and textual content and concurrently, share the annotations among its users. In addition, MobiTOP provides additional functionality such as clustering of annotations and advanced search and filtering options. A usability evaluation of the system was conducted in the context of a travel companion for tourists. The results suggested the potential of the system in terms of functionality for mobile content sharing. Participants agreed that the features in MobiTOP were generally usable as a content sharing tool. Implications and future work are also reported in this paper.